Fostering Engagement in Asynchronous Learning through Collaborative Multimedia Annotation - Counts, Scott; Grudin, Jonathan (IOS Press, 2001)
This paper presents an experimental test of a prototype system for asynchronous distance learning. The prototype allows viewers of audio and video to create and share text annotations that are synchronized with the multimedia. We extended the system to support group exercises and conducted an experimental study with three conditions: groups working asynchronously; groups working face-to-face; and individuals working alone. The results suggest that the use of group exercises can promote engagement and system use, and also suggest possible further improvements to the annotation system.